Kawasaki Disease: Contemporary Clinical Approaches and Challenges - Winnie K. Y. Chan (Rheumato, 2026)
Kawasaki disease (KD) is an acute, self-limiting systemic vasculitis that mainly affects young children. It is the leading cause of acquired heart disease in the developed world and is unique among childhood vasculitides for its predilection toward coronary artery involvement. This review describes the clinical spectrum of KD, highlighting diagnostic difficulties, especially in atypical presentations, and the challenges of managing treatment resistance. While intravenous immunoglobulin and aspirin remain the standard of care, especially in reducing coronary inflammation, early recognition and prompt therapy are crucial to preventing lifelong cardiac complications. To support this, various clinical risk scores have been developed over the decades to predict coronary artery lesions and IVIG resistance, enabling earlier intensification of treatment to prevent cardiac complications. Although the etiopathogenesis of KD remains unknown, extensive and robust research is ongoing to identify biomarkers, including epigenetic markers, innate and adaptive immunity activation markers, cytokine profiles, and to explore the influence of external triggers and the gut microbiome–immunity interplay. This review attempts to provide a concise overview of KD, aiming to assist clinicians in understanding the complexity of the problem rather than addressing all issues in detail.